IMPACT OF ASBESTOS EXPOSURE ON THE HEALTH OF THE ADULT POPULATION: AN INTEGRATIVE REVIEW - Fátima Denise Padilha Baran; Lara Adrianne Garcia Paiano; Nen Nalú Alves das Mercês (Universidade Federal do Paraná, 2016)
The objective of this study was to identify the impact of asbestos exposure on the health of the adult population in scientific publications. An integrative literature review was carried out in health databases in the period from 2005 to 2015. Fifteen studies were selected.The impact of asbestos exposure on the adult populationwas observed inthe onset of diseases such as malignant mesothelioma, asbestosis, and lung cancer.Mortality due to mesothelioma in workershad a significant prevalence for the study. Mortality ratesare alarming, considering that the therapeutic possibilities are limited. The impact of asbestos exposure surpasses biological aspects, bringing significant psycho-emotional changes to the health of the population. Therefore, it is important to discuss the asbestos impact on adult health, primarily in worker's health, regarding the need for banning its use in countries that still use it in industrial and commercial scale.